2022
DOI: 10.3389/fphar.2022.1011947
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of manganese-induced neurotoxicity and the pursuit of neurotherapeutic strategies

Abstract: Chronic exposure to elevated levels of manganese via occupational or environmental settings causes a neurological disorder known as manganism, resembling the symptoms of Parkinson’s disease, such as motor deficits and cognitive impairment. Numerous studies have been conducted to characterize manganese’s neurotoxicity mechanisms in search of effective therapeutics, including natural and synthetic compounds to treat manganese toxicity. Several potential molecular targets of manganese toxicity at the epigenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 223 publications
0
3
0
Order By: Relevance
“…Chronic exposure studies have ascertained the possible role of Mn in the etiopathogenesis of PD [72][73][74][75][76]. Similarly, Avila-Costa's group and our lab have shown that V can damage the nigrostriatal dopaminergic systems and different components of the CNS in rodents [37,[39][40][41], suggesting that V might also play a role in PD pathology and etiology.…”
Section: Discussionmentioning
confidence: 80%
“…Chronic exposure studies have ascertained the possible role of Mn in the etiopathogenesis of PD [72][73][74][75][76]. Similarly, Avila-Costa's group and our lab have shown that V can damage the nigrostriatal dopaminergic systems and different components of the CNS in rodents [37,[39][40][41], suggesting that V might also play a role in PD pathology and etiology.…”
Section: Discussionmentioning
confidence: 80%
“…However, studies on the association of these trace elements with the risk of all-cause mortality are rare. Numerous studies have been carried out to describe the neurotoxic mechanisms of manganese ( 38 , 39 ). Further studies are needed to explore the association between the dose–response relationship of these trace elements in the body and the risk of all-cause mortality and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is also suggested that manganese can impair the function of astrocytic glutamate transporters (glutamate transporter 1, GLT‐1 and glutamate aspartate transporter, GLAST) and glutamate uptake, leading to disruption of glutamate homeostasis and excitotoxic neuronal injury, eventually causing neurodegeneration (Fumagalli et al., 2008; Karki et al., 2015; Lee et al., 2009; Pajarillo et al., 2022).…”
Section: Assessmentmentioning
confidence: 99%
“…Since one of the roles of astrocytes is regulation of immune responses with production of cytokines and inflammatory mediators, several studies have shown that dysregulation of mitochondrial bioenergetics in astrocytes may result in neuroinflammation, leading to neuronal injury (Kirkley et al., 2017; Pajarillo et al., 2022; Sarkar et al., 2018; Verina et al., 2011; Zhao et al., 2009).…”
Section: Assessmentmentioning
confidence: 99%